CD exercises - Friederang, Steve (Cool digital swim videos)
This programme is perfect for novices, fitness swimmers, triathletes, parents, high school, college, world-class swimmers, teachers and coaches too. It filmed above, under, and "tracked" with Mike O'brien's Track Video. It also include verbal explanations by author and coach Steve Friederang. You may also find any movie instantly with the built in search functions, study 1 frame at a time, forward or backward, compare movies side by side, print 40,000 pictures, copy and paste frames and movies and includes Free Quick Time 3.0, Portfolio Browser and Cool Coach Demo.